PODER LOCAL: A CÃMARA MUNICIPAL NO BRASIL E EM PORTUGAL - FERNANDES CASTILHO, José Roberto (Revista Tópos, 2013)
Trata-se de estudo de Direito Constitucional Comparado luso-brasileiro referente ao Município. O texto analisa, comparativamente, a esfera local do poder político, no Brasil e em Portugal, considerando que o Município brasileiro constitui notória herança portuguesa. Mostra que a Câmara Municipal corresponde a órgãos distintos nos dois Estados, que têm, atualmente, forma de Estado diferenciada. No Brasil, uma federação, ela indica o órgão legislativo do poder local enquanto em Portugal, um Estado unitário, o executivo local é colegiado e tem o mesmo nome. Aponta as mudanças e reformas pelas quais tem passado a estrutura do ente local ao longo da história e, afinal, em conclusão, formula quadros comparativos. Palavras Chave: Poder Local, Direito Constitucional Comparado. LOCAL POWER: A TOW HALL IN BRAZIL AND PORTUGAL Abstract This study covers the Portuguese-Brazilian Compared Constitutional Law concerning the County. The text comparatively analyses the local sphere of the political power in Brazil and in Portugal, taking into account that the Brazilian County constitutes a notorious Portuguese heritage. In addition, this study demonstrates that the County Chamber corresponds to different organs in both States, Which currently have differentiated forms of State. In Brazil, which is a federation, the Chamber comprehend the legislative organ of the local power whereas in Portugal , which is a unitarian State, the local executive is a collegiate organ and has the same name. This study also points out the changes and reforms through which the structure of the local institution has passed along history and, in conclusion, it formulates comparative pictures. Keywords: Local Power, Compared Constitutional Law.